Fenomena Kawin Kontrak di Jabal Puncak: Perspektif Hak Asasi Manusia dan Pencegahan Tindak Pidana Perdagangan Orang sebagai Isu Hukum Kontemporer - Rahma Aliansya Ningrum; Mia Amalia; Aji Mulyana (Indonesian Journal Publisher, 2025)
The phenomenon of contract marriage is a temporary marriage practice commonly occurring in the Jabal Puncak area, involving foreign tourists—particularly from the Middle East—and local women. This practice is often conducted without official registration, leading to various legal and social issues. This research aims to analyze contract marriage from legal and human rights perspectives, as well as examine its connection to the criminal offense of human trafficking (TPPO). The study employs a qualitative approach using literature review methods and analysis of relevant legal and social cases. Data is obtained from legal documents, NGO reports, investigative news. The findings indicate that contract marriage involves the exploitation of women, including violations of their rights to legal protection, economic welfare, and human dignity. This practice is often viewed as a form of disguised prostitution that exploits legal loopholes and weak law enforcement oversight. Although Indonesia has regulations such as Law No. 1 of 1974 on Marriage and the Law on the Eradication of TPPO, their implementation remains suboptimal. In conclusion, this research emphasizes the need for stricter legal reforms, rigorous oversight, and economic empowerment and education programs.